2019
DOI: 10.1016/j.omtn.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of miR-126a Promotes Hepatic Aging and Inflammation in a Mouse Model of Cholestasis

Abstract: MicroRNAs (miRNAs) act as regulators of aging at the tissue or organism level or as regulators of cellular senescence. Targeted deletion of miR-126 in mice causes partial embryonic lethality, but its biological function in the liver is still largely unknown. Here, we deleted miR-126a , using the CRISPR/Cas9 system in vitro and in vivo . miR-126a was reduced in the aging livers, and disruption of miR-126a in bone mesenchymal stem cells (BMSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
1
14
0
1
Order By: Relevance
“…9,10 Meanwhile, miRNAs play important roles in the mediation of gene expression. [11][12][13] It has been shown that miRNAs have emerged as key regulators during the development of cancer initiates, and play vital roles in tumor growth, biosynthesis, and drug resistance. 14 Zhao et al indicated that miRNAs acted as novel chemo-resistance regulators, which could regulate the levels of drug resistance-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Meanwhile, miRNAs play important roles in the mediation of gene expression. [11][12][13] It has been shown that miRNAs have emerged as key regulators during the development of cancer initiates, and play vital roles in tumor growth, biosynthesis, and drug resistance. 14 Zhao et al indicated that miRNAs acted as novel chemo-resistance regulators, which could regulate the levels of drug resistance-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Using polyinosinic-polycytidylic acid (poly I:C) and lipopolysaccharide (LPS) to activate TLR3 and TLR4, respectively, we showed that the signaling cascade that includes TLR3 or TLR4, the TLR adaptor molecule, Trif, type I interferons (IFNs), and the type I IFN receptor (IFNAR1), increases versican expression by mouse macrophages, which implicates versican as an IFN-stimulated gene (60). Versican synthesis is also controlled by several different miRNAs which are modulated during inflammation (61)(62)(63).…”
Section: Versicanmentioning
confidence: 99%
“…Recent investigation has revealed that miRNAs are involved in liver regeneration and might serve as the therapeutic approach to liver fibrosis ( John et al., 2014 ; Tsay et al., 2019 ). Our previous research has shown that miR-126 contributes to hepatic anti-aging and damage repair ( Yan et al., 2019 ). To reveal the effect of miR-126 on anti-aging, we first detected the expression of stem cell-associated genes in C3H10 cells from which the miR- 126 has been deleted.…”
Section: Resultsmentioning
confidence: 99%
“…Two pairs of CRISPR guide RNAs (gRNAs) targeting pre-miR-126 gene were initially screened in NIH3T3cells. The gRNA targeting sgRNA3 displayed ∼50% mutagenesis at the on-target site in pre-miR-126 , as determined by PCR and a T7EN1 cleavage assay ( Yan et al., 2019 ). After targeting efficiency was confirmed, the sgRNAs were constructed into lentivirus and adenovirus plasmids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation